Bioarchaeology of Frontiers and Borderlands 2019
DOI: 10.5744/florida/9781683400844.003.0011
|View full text |Cite
|
Sign up to set email alerts
|

Mortuary Practices in the First Iron Age Romanian Frontier

Abstract: This chapter presents the bioarchaeological and zooarchaeological analysis of the Iron Age remains Măgura Uroiului. A combined analysis of this assemblage using similar methodologies allows for a fuller understanding of mortuary ritual at the site. Data indicate that mortuary activity of the First Iron Age in Transylvania was complex, and that the burials described were likely deposited intentionally as a part of the construction of the Măgura Uroiului monument. Ritual activities included feasting, animal sacr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Given a very complex assemblage that included both whole and partial human individuals and whole and partial animals (including the remains of feasting), consistently recording human and animal remains using a single recording methodology allowed us to compare body processing across species. The demographic conclusions were the most striking here: initial results indicated that only adult females and children between 6 and 10 years of age at death were included in the funerary monument, a pattern that would have been lost without careful recording (Osterholtz et al 2016). The discovery of a single adult male cranium during final data collection during the summer of 2016 indicates a complex mortuary assemblage that needs to be better contextualized and compared with additional Iron Age assemblages before an understanding of mortuary processes can be reached for the region.…”
Section: Development Of the Databasementioning
confidence: 83%
See 1 more Smart Citation
“…Given a very complex assemblage that included both whole and partial human individuals and whole and partial animals (including the remains of feasting), consistently recording human and animal remains using a single recording methodology allowed us to compare body processing across species. The demographic conclusions were the most striking here: initial results indicated that only adult females and children between 6 and 10 years of age at death were included in the funerary monument, a pattern that would have been lost without careful recording (Osterholtz et al 2016). The discovery of a single adult male cranium during final data collection during the summer of 2016 indicates a complex mortuary assemblage that needs to be better contextualized and compared with additional Iron Age assemblages before an understanding of mortuary processes can be reached for the region.…”
Section: Development Of the Databasementioning
confidence: 83%
“…The feature-based approach is quick and allows for field lab analysis that can keep pace with excavation. The minimum number of individuals (MNI) and demography of a commingled assemblage can serve as baseline data for subsequent research questions regarding health (e.g., Baustian 2010), violence (e.g., Osterholtz 2016), and mortuary processes (e.g., Osterholtz et al 2016), for example. It should be noted, however, that this database can be adapted to investigate research interests not represented by those listed here.…”
mentioning
confidence: 99%